The expression of immune response genes in patients with chronic Chagas disease is shifted toward the levels observed in healthy subjects as a result of treatment with Benznidazole - Gómez, Inmaculada; Egui, Adriana; Palacios, Génesis; Carrilero, Bartolomé; Benítez, Celia; Simón, Marina; Segovia, Manuel; Carmelo, Emma; López, Manuel Carlos; Thomas, M. Carmen (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionChagas disease, caused by the Trypanosoma cruzi parasite infection, is a potentially life-threatening neglected tropical disease with a worldwide distribution. During the chronic phase of the disease, there exists a fragile balance between the host immune response and parasite replication that keeps patients in a clinically-silent asymptomatic stage for years or even decades. However, in 40% of patients, the disease progresses to clinical manifestations mainly affecting and compromising the cardiac system. Treatment is recommended in the chronic phase, although there are no early markers of its effectiveness. The aim of this study is to identify differential expression changes in genes involved in the immune response in antigen-restimulated PBMC from chronic patients with Chagas disease due to benznidazole treatment.MethodsThus, high-throughput real-time qPCR analysis has been performed to simultaneously determine global changes in the expression of 106 genes involved in the immune response in asymptomatic (IND) and early cardiac manifestations (CCC I) Chagas disease patients pre- and post-treatment with benznidazole.Results and discussionThe results revealed that 7 out of the 106 analyzed genes were differentially expressed (4 up- and 3 downregulated) after treatment in IND patients and 15 out of 106 (3 up- and 12 downregulated) after treatment of early cardiac Chagas disease patients. Particularly in CCC I patients, regulation of the expression level of some of these genes towards a level similar to that of healthy subjects suggests a beneficial effect of treatment and supports recommendation of benznidazole administration to early cardiac Chagas disease patients. The data obtained also demonstrated that both in asymptomatic patients and in early cardiac chronic patients, after treatment with benznidazole there is a negative regulation of the proinflammatory and cytotoxic responses triggered as a consequence of T. cruzi infection and the persistence of the parasite. This downregulation of the immune response likely prevents marked tissue damage and healing in early cardiac patients, suggesting its positive effect in controlling the pathology.